Victories greater than death - Anders, Charlie Jane (Tor Teen, 2022)
Tired of hiding in obscurity on Earth, Tina, the human clone of a brilliant alien tactician, pursues her destiny in space, but success is elusive until Tina and her best friend Rachael assemble a ragtag crew of humans and set out to save all the worlds.